A new design of high output voltage rectifier for rectenna system at 2.45 GHz - Abdellah Taybi; A. Tajmouati; J. Zbitou; A. Errkik; M. Latrach; L. El Abdellaoui (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper deals with the design and achievement of a novel microstrip rectifier with high conversion efficiency and output voltage. Firstly, we have designed a rectifier based on HSMS2820 Schottky diodes by using a series topology to convert the electromagnetic energy into DC power. Then, a stepped-impedance low pass filter was implemented to filter the unwanted harmonics generated by the non-linear Schottky diode. Both of the structures have been simulated and fabricated on an FR4 substrate with dielectric permittivity constant 4.4, thickness of 1.6 mm and loss tangent of 0.025. Good performances were confirmed throughout the measurement results and an interesting output voltage was observed.